INHIBITION OF WIL-2 NS CELLS PROLIFERATION IS RELATED TO G2/M ARREST AND INDUCTION OF CASPASE-MEDIATED APOPTOSIS - Mbazima, V. G.; Mokgotho, M. P.; Masoko, P.; Howard, R. L.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Commelina benghalensis L. is an annual or perennial herb with fleshy creeping stems that root readily at the nodes. The plant is used in the eastern and northern parts of South Africa as a crude medicinal agent in the treatment of stomach disorders, skin lumps and/or on cancerous skin outgrowths. We have evaluated CMECB for its possible chemopreventative application in vitro by studying its role in the regulation of proliferation, cell division cycle and apoptosis in Wil-2 NS cancer cell line. CMECB inhibited cell proliferation and induced G2/M arrest and apoptosis in Wil-2 NS cells. CMECB-induced apoptosis of Wil-2 NS cells is mediated via the modulation of the intrinsic apoptotic pathway. Up-regulation and phosphorylation of p53 resulted in the down regulation of the anti-apoptotic protein Bcl-2. The altered expression of Bcl-2 triggered the release of cytochrome c and activation of caspase-9 followed by activation of effector caspase-3 thus leading to PARP cleavage and apoptosis. In conclusion, CMECB exerts its anti-neoplastic effects by modulating the cell cycle and apoptosis regulatory genes. Acknowledgements: National Research Foundation (NRF) and the University of Limpopo senate research fund for financial support.